Factors Affecting Company Capital Structure with Business Risk as a Moderator - Wijaya, Richad (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
This study aims to obtain empirical evidence of the effect of profitability, reliability, asset growth, liquidity, and non-debt tax shield on capital structure. This study uses business risk as a moderator. This study uses samples from manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019, and then samples were selected by purposing a sampling method. The final observations were 202, which fulfilled all the criteria, consisting of 59 companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The methods of analysis used in this research are quantitative and multiple regression analysis. The results showed that tangibility and liquidity had a negative effect on the capital structure, and the non-debt tax shield had a positive effect. The results of this study also show that business risk cannot weaken the positive effect of tangibility on capital structure, and business risk cannot strengthen the negative effect of liquidity and non-debt tax shields on capital structure.